Unravelling the potent anti-oxidant and anti-inflammatory actions of plumbagin: A review of preclinical discoveries - Aanchal Verma; Ahsas Goyal (Elsevier, 2024)
Introduction: Bioactive elements present in distinct medicinal plants and foods are appealing molecules for the evolution of novel medications for the treatment of multiple illnesses linked with inflammation and oxidative stress. The majority of these bioactive compounds exert a significant suppressive action on inflammation and oxidative stress. Intake of a diet high in such compounds may help people to enhance their life's quality. Plumbagin is a primary component of Baihua Dan, a traditional Chinese medicine that is derived from the roots of the medicinal herb Plumbago zeylanica L. This review briefly discusses the chemical properties, pharmacokinetics, quantification and structural activity relationship of plumbagin as well as gives an overview of its beneficial antioxidant and anti-inflammatory functions in several pathological conditions. Methodology: Relevant studies were identified through electronic searches of Pubmed, Scopus, Web of Science and Google scholar. The search used the terms "Plumbagin" "Napthoquinone" or "Plumbago zeylanica" paired with "Oxidative stress" "Oxidation" "Inflammation" "Antioxidant" and "Anti-inflammatory". In addition, we searched the bibliographies of relevant studies and reviews between 1980 and 2023 for articles in English. Results: The findings included in this study demonstrate that plumbagin offers antioxidative and anti-inflammatory benefits. Hence, plumbagin shows promise as a potential treatment or means of managing chronic diseases associated with increased oxidation and inflammation because of its valuable capacity to inhibit oxidative stress and inflammation. Discussion: Plumbagin exhibits a wide variety of pharmacological activities including anticancer, anti-inflammatory, anti-diabetic, antioxidant, antibacterial, antifungal, anti-atherosclerosis, and analgesic activities. Conclusion: Since, increased oxidative stress and neuroinflammation are primarily associated with the onset of disorders including cancer, diabetes, arthritis and several chronic disorders of the brain, liver and heart, plumbagin appears to be a viable therapeutic agent for the treatment or control of such chronic diseases due to its valuable inhibitory actions on oxidative stress and inflammation.